The Importance of Organizational Culture and Organizational Climate in Improving Motivation and Performance: A Theoritical Review - Putri, Haliza Nabila; Agustina, Tri Siwi; Ekowati, Dian (Equator Journal of Management and Entrepreneurship (EJME), 2025)
This study analyzes the influence of organizational culture, organizational climate, and motivation on employee performance through the literature review method. The results show that a strong organizational culture (results-oriented, collaboration, innovation) and a conducive organizational climate (open communication, management support, reward system) have a significant effect on improving performance. Work motivation (intrinsic and extrinsic) also proved to be a key factor, both as a direct influence and as an intervening variable. The findings reveal that organizational culture and climate not only have a direct impact on performance, but also indirectly through motivation. The practical implication is that organizations need to build a clear culture, strengthen the positive work climate, and design holistic motivation programs. The role of leaders as role models and HR policies that focus on employee development are also supporting factors.